2020
DOI: 10.1002/cnma.202000272
|View full text |Cite
|
Sign up to set email alerts
|

Hollow‐Structured Electrode Materials: Self‐Templated Synthesis and Their Potential in Secondary Batteries

Abstract: Hollow‐structured electrode materials have found broad applications in secondary batteries. The built‐in cavity of the prepared materials shows favorable features such as structural stability against volumetric deformation, good reservoir for electrolyte, and fast charge transport kinetics, which are highly efficient to improve the electrochemical performance of the electrode materials, particularly their cycling stability and high rate capability. However, the full potential of hollow‐structured materials is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 112 publications
0
8
0
Order By: Relevance
“…Considering the advantages of mechanical stability, large surface area, and high specific capacity for self-supported nanostructured electrodes, Zhu et al reported a simple strategy to in situ construct Bi nanosheets by using BiOCl as the primary template (T-BiNS, Figure 4). [73,74] The rhombohedral Bi was transformed from BiOCl via cyclic voltammetry (CV) in the potential range of À 1.5-0.2 V at a scan rate of 5 mV s À 1 . DFT calculation indicates that the space for T-BiNS (corresponding to Bi) after topotactic transformation (57.6%) is much larger than that for Bi 2 O 3 (19.2%).…”
Section: Bi For Aqueous Alkaline Batteriesmentioning
confidence: 99%
“…Considering the advantages of mechanical stability, large surface area, and high specific capacity for self-supported nanostructured electrodes, Zhu et al reported a simple strategy to in situ construct Bi nanosheets by using BiOCl as the primary template (T-BiNS, Figure 4). [73,74] The rhombohedral Bi was transformed from BiOCl via cyclic voltammetry (CV) in the potential range of À 1.5-0.2 V at a scan rate of 5 mV s À 1 . DFT calculation indicates that the space for T-BiNS (corresponding to Bi) after topotactic transformation (57.6%) is much larger than that for Bi 2 O 3 (19.2%).…”
Section: Bi For Aqueous Alkaline Batteriesmentioning
confidence: 99%
“…SPP materials are widely known for a variety of applications such as in hollow silica spheres for drug delivery, microreactors, catalysis, and batteries (Caruso et al, 1998;Huang et al, 2011;Lu et al, 2020;Takai-Yamashita & Fuji, 2020). However, these applications and production methods will not be discussed in this review because these topics are not related to chromatography.…”
Section: Methods For Producing Sppsmentioning
confidence: 99%
“…They have low density, high surface-to-volume ratio, and abundant internal space, and have a high capacity to accept guest species due to their high mass-to-volume ratio. 1–8…”
Section: Introductionmentioning
confidence: 99%
“…They have low density, high surface-to-volume ratio, and abundant internal space, and have a high capacity to accept guest species due to their high mass-to-volume ratio. [1][2][3][4][5][6][7][8] Considering that hollow nanostructures play the role of catalysts, 9 they can provide internal and external surfaces for reaction sites. Hollow nanostructures have also been created in prismatic, cubic, and polyhedral shapes, in addition to the more typical tubular and spherical ones.…”
Section: Introductionmentioning
confidence: 99%